(untitled) (Research, Society and Development, 2022)
The goals of this study consisted of the development and application of a methodology aimed at identifying college students with a higher risk of dropping out during the covid -19 pandemic and the proposal of actions reducing this risk. We used snowball sampling and contact networks to understand how to act to enhance academic motivation. A quantitative action-research methodology was applied to the community of students from STEM courses at CCET/UNIRIO and, with the data collected, we identified students that could have a higher dropout risk. We verified that 50% of responding students pointed out that changes in their personal lives caused by the covid -19 pandemic could prevent the continuity of their studies, this being the main dropout risk identified. Also, 41% of responding students identified a lack of academic motivation as a reason for dropout. From this and additional information, we were able to evaluate how connected and engaged with their academic lives these students were and identify actions that could contribute to maintaining their bond with the university. Finally, we held welcoming and dialogue events featuring teachers, staff, and students, in an attempt to reduce the dropout risk of the identified students. These events highlighted the students’ expectations for more dialogue in the classroom, which supported the follow-up of the project.